Influence of Low Molecular Weight Heparin and Low Molecular Weight Dextran Sulfate on the Inhibition of Coagulation Factor XIa by Serpins - Mauron, Thomas; Lämmle, Bernhard; Wuillemin, Walter A. (Thrombosis and Haemostasis, 1998)
We investigated the influence of low molecular weight dextran sulfate (LMWdxs) and low molecular weight heparins (LMWH: dalteparin, enoxaparin and nadroparin) on the inhibition of FXIa by C1-inhibitor, α1-antitrypsin, α2-antiplasmin and antithrombin in a purified system and in plasma.The second order rate constant for inactivation of FXIa by C1-inhibitor, α1-antitrypsin, α2-antiplasmin, and antithrombin was 1.23, 0.056, 0.33 and 0.59 × 103 M–1 s–1, respectively.LMWdxs and LMWH dose-dependently increased the second order rate constant of the inactivation of FXIa by C1-inhibitor up to 39-fold. The second order rate constant of the inactivation of FXIa by anti-thrombin was increased up to 6-fold by LMWH, whereas LMWdxs had no effect. In plasma, FXIa was inactivated to about 50% by C1-inhibitor, while the other serpins contributed together to the remaining 50% of plasma’s inhibitory capacity towards FXIa. In the presence of LMWdxs or LMWH, FXIa was inactivated in plasma to more than 90% by C1-inhibitor. LMWH at maximal therapeutic plasma levels enhanced the contribution of antithrombin to the inactivation of FXIa in plasma up to 5-fold.In conclusion, we found that the tested low molecular weight glycosaminoglycans dalteparin, enoxaparin and nadroparin and LMWdxs stimulate inactivation of FXIa by C1-inhibitor in a system using purified proteins as well as in plasma. Furthermore, LMWH but not LMWdxs slightly enhanced FXIa inhibition by antithrombin.